Split-root systems: detailed methodology, alternative applications, and implications at leaf proteome level - Saiz-Fernández, Iñigo; Černý, Martin; Skalák, Jan; Brzobohatý, Břetislav (Plant methods, 2021)
BACKGROUND: Split-root systems (SRS) have many applications in plant sciences, but their implementation, depending on the experimental design, can be difficult and time-consuming. Additionally, the system is not exempt from limitations, since the time required for the establishment of the SRS imposes a limit to how early in plant development experiments can be performed. Here, we optimized and explained in detail a method for establishing a SRS in young Arabidopsis thaliana seedlings, both in vitro and in soil. RESULTS: We found that the partial de-rooting minimized the recovery time compared to total de-rooting, thus allowing the establishment of the split-root system in younger plants. Analysis of changes in the Arabidopsis leaf proteome following the de-rooting procedure highlighted the distinct metabolic alterations that totally and partially de-rooted plants undergo during the healing process. This system was also validated for its use in drought experiments, as it offers a way to apply water-soluble compounds to plants subjected to drought stress. By growing plants in a split-root system with both halves being water-deprived, it is possible to apply the required compound to one half of the root system, which can be cut from the main plant once the compound has been absorbed, thus minimizing rehydration and maintaining drought conditions. CONCLUSIONS: Partial de-rooting is the suggested method for obtaining split-root systems in small plants like Arabidopsis thaliana, as growth parameters, survival rate, and proteomic analysis suggest that is a less stressful procedure than total de-rooting, leading to a final rosette area much closer to that of uncut plants. Additionally, we provide evidence that split root-systems can be used in drought experiments where water-soluble compounds are applied with minimal effects of rehydration.
Keywords: Drought stress; Arabidopsis thaliana; Proteomics; Split-root systems; Phytohormones